Doctor, there's a lump in my mouth!: imaging aspects of torus palatinus; a case report - Azni, Khaulah Karimah; Bahari, Norafida; Suppiah, Subapriya; Ahmad Saad, Fathinul Fikri; Mohamad Saini, Suraini (Community Health Society Malaysia, 2018)
This is a case report of a 36-year-old lady who presented with a swelling on the hard palate of her mouth. She had undergone computed tomography (CT) scan of the oropharynx and paranasal sinuses and the diagnosis of torus palatinus, a normal anatomical variant of the hard palate was made. The authors discuss about the appearance of torus palatinus in various imaging modalities, specifically dental radiograph, CT scan and magnetic resonance imaging (MRI).